Given that \( f(x)=(x-6)^{2} \) and \( g(x)=1-3 x \), find (a) \( (f+g)(x)=\square \) (b) \( (f-g)(x)=\square \) (c) \( (f g)(x)=\square \) (d) \( \left(\frac{f}{g}\right)(x)=\square \) Question Help: Video
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To solve the problem, let's first find the expressions for \( f(x) \) and \( g(x) \). Given: - \( f(x) = (x-6)^2 \) - \( g(x) = 1 - 3x \) Now, we'll compute each part step by step. (a) \( (f+g)(x) \): \[ (f+g)(x) = f(x) + g(x) = (x-6)^{2} + (1 - 3x) \] Expanding \( f(x) \): \[ (x-6)^2 = x^2 - 12x + 36 \] So, \[ (f+g)(x) = x^2 - 12x + 36 + 1 - 3x = x^2 - 15x + 37 \] (b) \( (f-g)(x) \): \[ (f-g)(x) = f(x) - g(x) = (x-6)^{2} - (1 - 3x) \] Continuing with our previous expansion for \( f(x) \): \[ (f-g)(x) = (x^2 - 12x + 36) - (1 - 3x) = x^2 - 12x + 36 - 1 + 3x \] Thus, \[ (f-g)(x) = x^2 - 9x + 35 \] (c) \( (fg)(x) \): \[ (fg)(x) = f(x) \cdot g(x) = (x - 6)^{2} \cdot (1 - 3x) \] Expanding this gives: \[ fg(x) = (x^2 - 12x + 36)(1 - 3x) \] Using the distributive property: \[ = (x^2)(1) - (x^2)(3x) - (12x)(1) + (12x)(3x) + (36)(1) - (36)(3x) \] This simplifies to: \[ = x^2 - 3x^3 - 12x + 36 - 108x \] Combining like terms: \[ = -3x^3 + x^2 - 120x + 36 \] (d) \( \left(\frac{f}{g}\right)(x) \): \[ \left(\frac{f}{g}\right)(x) = \frac{f(x)}{g(x)} = \frac{(x-6)^{2}}{1-3x} \] This is already in a simplified form, so we leave it as: \[ \left(\frac{f}{g}\right)(x) = \frac{(x-6)^{2}}{1 - 3x} \] In summary: (a) \( (f+g)(x) = x^2 - 15x + 37 \) (b) \( (f-g)(x) = x^2 - 9x + 35 \) (c) \( (fg)(x) = -3x^3 + x^2 - 120x + 36 \) (d) \( \left(\frac{f}{g}\right)(x) = \frac{(x-6)^{2}}{1-3x} \)